Publishing with Asia in Focus: Insights and Advice from the Editors - Committee, The Editorial (Asia in Focus, 2017)
We, the Editorial Committee, have been giving some thought as to the meaning of Asia in Focus. From the side of our contributors, we have considered: What are the opportunities presented for early-career researchers? How can publishing with us benefit them? From the editorial side, we have pondered: Why are we editors here? What are our concerns about the submissions we receive? What are the highlights during the review process? What further advice can we give to our contributors and readers? Instead of keeping the answers to these questions to ourselves, we would like to share, as we view the responses as useful knowledge that may further assist early-career researchers in their academic careers as well as inform a wider public of the situation scholars are in.